Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1021/bi00035a009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Dihydrofolate Reductase-Folate Complex: Catalytic Sites and Regions Known To Undergo Conformational Change Exhibit Diverse Dynamical Features

Abstract: Backbone and tryptophan side-chain dynamics of uniformly 15N-labeled Escherichia coli dihydrofolate reductase were determined for the binary folate complex. The 15N T1 and T2 relaxation times and [1H]-15N heteronuclear NOEs were measured for 118 protonated backbone nitrogen atoms. The generalized order parameter (S2), the effective correlation time for internal motions (tau e), and the contribution to spin-spin relaxation through 15N exchange broadening (Rex) were determined for each residue by model-free anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
148
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 62 publications
9
148
0
2
Order By: Relevance
“…Previous spin relaxation studies revealed large-amplitude picosecond-to-nanosecond time scale motions of the Met-20 loop in the occluded states of the enzyme that are abrogated upon loop closure (4,17,18). These studies also hinted at changes in microsecond-tomillisecond time scale motions that are potentially relevant to catalysis.…”
mentioning
confidence: 95%
“…Previous spin relaxation studies revealed large-amplitude picosecond-to-nanosecond time scale motions of the Met-20 loop in the occluded states of the enzyme that are abrogated upon loop closure (4,17,18). These studies also hinted at changes in microsecond-tomillisecond time scale motions that are potentially relevant to catalysis.…”
mentioning
confidence: 95%
“…Protein dynamics on the ps-ns and ÎŒs-ms timescales have been examined for a number of DHFR complexes by using NMR-based techniques (12)(13)(14)(15)(16)(17). The E:FOL and E:FOL: 5â€Č,6â€Č-dihydroNADPH (DHNADPH) complexes are both in the occluded conformation and display very similar ps-ns backbone dynamics that differ from those of the closed E:FOL:NADP ĂŸ complex (16).…”
mentioning
confidence: 99%
“…To this day, only a small number of enzymes have been shown to rely on essential proximal and/or distal coupled residue motions for catalysis, among which dihydrofolate reductase (5)(6)(7)(8), cyclophilin A (9, 10), liver alcohol dehydrogenase (11)(12)(13)(14), triose-phosphate isomerase (15)(16)(17)(18)(19), and ribonuclease A (20 -22) remain some of the best characterized systems (for recent reviews see Refs. 23 and 24).…”
mentioning
confidence: 99%